Design of Ammonia Gas Measurement System using TGS-826 Sensor, Arduino Nano Microcontroller, 16x2 LCD, and Micro SD Module - Junaidi, Ach; Rakhmadi, Frida Agung; Melati, Asih; Triyana, Kuwat (Proceeding International Conference on Science and Engineering, 2020)
Design of ammonia gas measurement system using TGS-826 sensor, Arduino Nano microcontroller, 16x2 LCD and micro SD module has been successfully carried out. Design was created with the help of SketchUp application. System design that has been made consists of ammonia adsorption chamber and electronic components in the form of a TGS-826 sensor, Arduino Nano microcontroller, 16x2 LCD and micro SD module. Working principle of the system that has been designed begins with the active sensor TGS-826 in detecting ammonia gas. Output from the sensor is then forwarded to the Arduino Nano microcontroller for processing. Processed data is then displayed by 16x2 LCD and the ammonia gas measurement data will automatically be stored in the micro SD module. Results of this design will make it easier in making the system.